2017
DOI: 10.1177/0361684317725985
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Disruption

Abstract: In research using self-report measures, there is little attention paid to how participants interpret concepts; instead, researchers often assume definitions are shared, universal, or easily understood. I discuss the self-anchored ladder, adapted from Cantril's ladder, which is a procedure that simultaneously collects a participant's self-reported rating and their interpretation of that rating. Drawing from a study about sexual satisfaction that included a self-anchored ladder, four analyses are presented and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 76 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Research from Levant et al (1998) found that most differences in the endorsement of traditional masculinity ideologies (e.g., avoidance of femininity, being aggressive, achieving status) were between Black and White men living in the U.S. South whereas in other geographic regions, Black men were only more traditional than White men on self-reliance. Moreover, these studies have primarily employed quantitative methodology to compare Black and White men’s endorsement of traditional masculinity, which may overlook subtle—yet critical—variations in meaning (see McClelland, 2017, for further discussion). More research using qualitative methods is needed to detect nuanced ways in which Black and White men view manhood, as well as to understand the role of power in these perceptions.…”
Section: Race and Perceptions Of Manhoodmentioning
confidence: 99%
“…Research from Levant et al (1998) found that most differences in the endorsement of traditional masculinity ideologies (e.g., avoidance of femininity, being aggressive, achieving status) were between Black and White men living in the U.S. South whereas in other geographic regions, Black men were only more traditional than White men on self-reliance. Moreover, these studies have primarily employed quantitative methodology to compare Black and White men’s endorsement of traditional masculinity, which may overlook subtle—yet critical—variations in meaning (see McClelland, 2017, for further discussion). More research using qualitative methods is needed to detect nuanced ways in which Black and White men view manhood, as well as to understand the role of power in these perceptions.…”
Section: Race and Perceptions Of Manhoodmentioning
confidence: 99%